A day no pigs would die. - Peck, Robert Newton (New York : Knopf, 1987)
To a thirteen-year-old Vermont farm boy whose father slaughters pigs for a living, maturity comes early as he learns "doing what's got to be done," especially regarding his pet pig who cannot produce a litter.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
5.0
5-8.
5-8
Keywords: Farm life -- Vermont -- Fiction; Fathers and sons -- Fiction; Pigs -- Fiction; Farm life -- Fiction; Fathers and sons -- Fiction; Pigs -- Fiction